Environmental Cost Analysis of PT. Gudang Garam Tbk - Distiawati, Rania Putri; Wardhana, Ery Tri Djatmika Rudijanto Wahju; Handayati, Puji (AIBPM Publisher, 2021)
In CSR activities, the initial concept of these activities is called the triple bottom line which consists of three corporate responsibilities in its business operations including people, planet, and profit. The data analysis technique used in this study is descriptive and comparative analysis of the sustainability report. The three aspects in the triple bottom line concept of CSR activities are the company's responsibility with the people, or the surrounding community by making social activities, corporate responsibility with the planet in various ways to overcome water, air, and soil waste. The last one is the company responsibility for profit that is also obtained from the good image which makes consumers become loyal customers of the company.